My share of the task a memoir - McChrystal, Stanley A. (New York Portfolio, 2014)
In early March 2010, General Stanley McChrystal, the commanding officer of all U.S. and coalition forces in Afghanistan, walked with President Hamid Karzai through a small rural bazaar. As Afghan townspeoƯple crowded around them, a Taliban rocket loudly thudded into the ground some distance away. Karzai looked to McChrystal, who shrugged. The two leaders continued greeting the townspeople and listening to their views.
Includes bibliographical references (p. 399-439) and index.
Keywords: McChrystal, Stanley A